1319 nm and 1356 nm dual-wavelength operation of diode-side-pumped Nd:YAG laser. (May 2016) - Chen, Ming; Wang, Zhi-chao; Zhang, Shen-jin; Yang, Feng; Zhang, Feng-feng; Yuan, Lei; He, Miao; Li, Jia-jia; Zhang, Xiao-wen; Zong, Nan; Wang, Zhi-min; Bo, Yong; et al.
Abstract: We report the first demonstration on a diode-side-pumped quasi continuous wave (QCW) dual-wavelength Nd:YAG laser operating at 1319 nm and 1356 nm. The resonator adopts symmetrical L-shaped flat–flat structure working in a thermally near unstable cavity. By precise coating on the cavity mirrors, the simultaneous oscillation at 1319 nm and 1356 nm is delivered. A maximum dual-wavelength output power of 9.4 W is obtained. The beam quality factor M 2 is measured to be 1.9. Highlights: We first report a dual-wavelength Nd:YAG laser operating at 1319 and 1356 nm. This dual-wavelength laser is delivered by precise coating on the cavity mirrors. Our scheme provides a novel way to obtain a radiation source of 6.2 THz.